(untitled) (Annals of Medical Research, 2021)
Aim: We evaluated the prevalence of Respiratory syncytial virus (RSV), the rates of hospitalization and intensive care unit (ICU) admission due to RSV infection, the need for mechanical ventilation, and the efficacy of palivizumab prophylaxis in children with congenital heart disease (CHD).Material and Methods: A total of 419 patients under 2 years old who were hospitalized with lower respiratory tract infection (LRTI) were included in this study. Patients were divided into two groups according to the presence of CHD. 241 patients had unstable CHD and 178 patients had no underlying conditions. Palivizumab prophylaxis was administered to 29 of the patients with CHD and RSV infection; 22 of these patients were followed for 1 year.Results: RSV infection was detected in 19.5% of the patients with CHD and in 20% of those without CHD. Among the 241 patients with CHD and LRTIs, the rate and duration of hospitalization for RSV were 14% and 9.9 days, respectively. The rate of admittance to the ICU was 32% and that of mechanical ventilation was 19% in the CHD patients with RSV infection. Of the patients without CHD, 12% were admitted to the ICU and 8% received mechanical ventilation. These rates were significantly higher among the RSV-infected patients with CHD. The rates of hospitalization for RSV before and after palivizumab prophylaxis were 59% and 14%, respectively; the difference was significant. Conclusion: RSV infection is a common cause of mortality and morbidity in patients with CHD; palivizumab prophylaxis is effective in these patients.